Design of Electric Steering Wheel for Agricultural Machinery. (July 2020) - Li, Yueyang; Deng, Wenzhi; Cheng, Xiaofei; Song, Weihai; Li, Zhen; Zhang, Xianchong
Abstract: Aiming at the automatic steering control system of agricultural machinery, this paper puts forward the method of using S7-200 intelligent PLC of Siemens company as the core controller, which uses the high-speed pulse signal output by the controller to control the stepper motor to drive the rotation of the steering shaft, realizes the automatic steering through the control of the motor speed and steering, uses the encoder to detect the rotation angle of the steering shaft to realize the feedback control, and selects the touch screen to realize the user interaction scheme.